1994
DOI: 10.1164/ajrccm.149.5.8173779
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of tuberculosis and tuberculosis infection in adults and children. American Thoracic Society and The Centers for Disease Control and Prevention.

Abstract: Treatment of Tuberculosis. 1. A 6-mo regimen consisting of isoniazid, rifampin, and pyrazinamide given for 2 mo followed by isoniazid and rifampin for 4 mo is the preferred treatment for patients with fully susceptible organisms who adhere to treatment. Ethambutol (or streptomycin in children too young to be monitored for visual acuity) should be included in the initial regimen until the results of drug susceptibility studies are available, unless there is little possibility of drug resistance (i.e., there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
114
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 968 publications
(114 citation statements)
references
References 0 publications
0
114
0
Order By: Relevance
“…Hepatic damage is rare in patients less than 20 years old; it is observed in 0.3% of those in the 20-34 years age group, increasing to 1.2% in the 35-49 years age group and 2.3% in those older than 50 years of age. 26,27,[32][33][34] Up to 12% of patients receiving INH may have elevated plasma aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities. 32,33 Recent treatment studies have reported significant transaminase elevation in 1-4% of those treated with INH for latent tuberculosis infection.…”
Section: First-line Drugs Isoniazidmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic damage is rare in patients less than 20 years old; it is observed in 0.3% of those in the 20-34 years age group, increasing to 1.2% in the 35-49 years age group and 2.3% in those older than 50 years of age. 26,27,[32][33][34] Up to 12% of patients receiving INH may have elevated plasma aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities. 32,33 Recent treatment studies have reported significant transaminase elevation in 1-4% of those treated with INH for latent tuberculosis infection.…”
Section: First-line Drugs Isoniazidmentioning
confidence: 99%
“…26,27,[32][33][34] Up to 12% of patients receiving INH may have elevated plasma aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities. 32,33 Recent treatment studies have reported significant transaminase elevation in 1-4% of those treated with INH for latent tuberculosis infection. [33][34][35][36] A meta-analysis of six studies estimated the rate of clinical hepatitis in patients given INH alone to be 0.6%.…”
Section: First-line Drugs Isoniazidmentioning
confidence: 99%
“…Therefore, there is a need to develop a sustained release formulation of ethionamide to improve compliance by reducing the dosing frequency and to improve therapeutic effectiveness. Furthermore, ethionamide is a poorly tolerated drug and often administered with meals to reduce gastrointestinal intolerance (Bass et al, 1994). Ethionamide also undergoes first pass metabolism which reduces its oral bioavailability (Auclair et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These drugs are often administered over a period of six months 3 and this prolonged treatment leads on occasions to the development of drug resistance. 4 Thus novel classes of antimycobacterials are urgently required which have modes of action that are divergent from those drugs used in current therapy.…”
Section: Introductionmentioning
confidence: 99%